The Endoscopic Modified Lothrop: Lessons Learned during a 17‐Year Experience. (2nd September 2014) - Leavitt, Kathryn A.; Rasband‐Lindquist, Allison N.; Robinson, Ann B.; Beahm, D. David; Hoover, Larry A.
Abstract : Objectives: Participants should be able to: (1) Recognize factors contributing to failure; (2) Describe techniques required for a safe/successful surgery; (3) Implement postsurgical medical treatment enhancing long term outcome. Methods: Results with the endoscopic Modified‐Lothrop were reviewed. Although the success rate is good for revision sinus surgery (90%), factors contributing to failure such as allergy, mucosal reactivity, and scar formation were investigated. The senior author's series of 104 endoscopic modified Lothrops completed between January 1997 and October 2013 were reviewed for patency of the frontal floor drainage, mucosal condition, and symptomatology. The Lothrop procedure was first reported in 1914 using an external incision. Draft in 1991, Close in 1994, and Gross in 1995 described the endoscopic modified Lothrop. All patients selected for this procedure had failed medical treatment of nasal saline and antiseptic irrigations, topical steroids, and appropriate antibiotics. Nearly all of these patients had also failed standard endoscopic sinus procedures at least once. Results: Image guidance has improved the precision and safety of this operation. Three of the first 5 procedures performed without image guidance failed. Of the succeeding 99 procedures performed with image guidance, 96% were successful in maintaining open frontal drainage and resolving most symptoms with a prolonged follow‐up (mean 42 months). Conclusions: The endoscopic modified Lothrop is a technically difficult procedure. When performed under the supervision of an experienced endoscopic surgeon with image guidance and modern endoscopic irrigated curved drills, it can be performed safely and effectively when standard endoscopic procedures fail.